Information Resilience Test Against Digital Image Manipulation and Online Media Sending in Steganography Using Least Significant Bit Algorithm - Aditya Aziz Fikhri; Nur Aynun Siregar; Nurdin (Faculty of Engineering, Malikussaleh University, 2024)
Steganography is a method of hiding information, which can be text, images, or videos, in a cover image, secret information is hidden in a way that is invisible to the eye. Steganography is designed to maintain hiding capacity while still considering security and insensitivity to steganalysis. One of the characteristics of steganography is robustness, which can maintain the information in it. So that robustness testing is very important in determining the effectiveness of the steganography algorithm used. This paper aims to test the resilience of information or messages hidden after inserting secret messages in stego images. In this study, the tests carried out include digital image manipulation and the process of sending stego image files. Various types of manipulation such as resizing, compression, and other visual effects. Then it will be explored to assess the extent to which the integrity of the message is maintained. This study resulted in tests carried out related to testing the storage capacity of the cover image greatly affecting each size, the process of sending stego images in PNG format on online media E-Mail, WhatsApp, and Telegram experienced changes in the size of the files received on each platform. However, the file extension does not change, which means there is no file format conversion on the three platforms. In terms of file size, there is a difference in file size on the three online media, but the difference does not affect the extraction of secret messages, which means the message extraction process is 100% successful. The digital image manipulation test carried out, namely crop, resize, brightness, rotate, and flip, most of the tests carried out failed in extracting text messages.